PENDEKATAN POSKOLONIAL TERHADAP DEKOLONIALISASI TEOLOGI MELALUI ANALISIS TIGA DIMENSI TEOLOGIS - Tampilang, Risno (STT-RAI Batam, 2025)
This study evaluates the relationship between postcolonial theory and theology, highlighting how colonial power structures still shape theological narratives in the postcolonial context. Postcolonial theology not only revises traditional approaches to sacred texts but also dismantles the hegemonic relations that construct epistemological hierarchies in religious discourse. Using a literature review method, this study analyzes how the concept of postcolonialism operates at three levels of theology: faith theology (first-order theology), deliberative theology (second-order theology), and academic theology (third-order theology). The results of this study found that the construction of the relationship between theology and postcolonialism moves in three reflective layers. First, theology that is inherent in the individual, namely the experience of faith formed in the body and consciousness of the individual, often contains hidden and real colonial traces. Second, theology that is reflected on in the community (church), as a space for sharing experiences and building a collective narrative that is able to treat historical wounds and fight for recovery. Third, theology that is discussed academically, namely a reflective-critical effort to challenge, dismantle, and reconstruct theological discourse through a cross-contextual approach and decolonial awareness.